Natural Antimicrobial Peptides and Their Synthetic Analogues for Effective Oral Microflora Control and Oral Infection Treatment—The Role of Ceragenins in the Development of New Therapeutic Methods - Michał Czarnowski; Urszula Wnorowska; Milena Łuckiewicz; Ewelina Dargiewicz; Jakub Spałek; Sławomir Okła; Beata Sawczuk; Paul B. Savage; Robert Bucki; Ewelina Piktel (Pharmaceuticals, 2024)
Oral diseases, both acute and chronic, of infectious or non-infectious etiology, represent some of the most serious medical problems in dentistry. Data from the literature increasingly indicate that changes in the oral microbiome, and therefore, the overgrowing of pathological microflora, lead to a variety of oral-localized medical conditions such as caries, gingivitis, and periodontitis. In recent years, compelling research has been devoted to the use of natural antimicrobial peptides as therapeutic agents in the possible treatment of oral diseases. This review focuses on the potential of ceragenins (CSAs), which are lipid analogs of natural antimicrobial peptides, as molecules for the development of new methods for the prevention and treatment of oral diseases. Studies to date indicate that ceragenins, with their spectrum of multidirectional biological activities, including antimicrobial, tissue regeneration-stimulating, anti-inflammatory, and immunomodulatory properties, are strong candidates for further development of oral formulations. However, many of the beneficial properties of ceragenins require confirmation in experimental conditions reproducing the oral environment to fully determine their application potential. Their transition to practical use also requires more advanced testing of these molecules in clinical trials, which have only been conducted in limited numbers to date.